1990
DOI: 10.1118/1.596483
|View full text |Cite
|
Sign up to set email alerts
|

A patient‐equivalent attenuation phantom for estimating patient exposures from automatic exposure controlled x‐ray examinations of the abdomen and lumbo–sacral spine

Abstract: The Joint Commission on Accreditation of Healthcare Organizations requires diagnostic radiology facilities to known the approximate amount of radiation received by an average patient during radiographic examinations at the facility. Automatic exposure controlled (AEC) techniques are used for many of these exams, and a standard patient-equivalent phantom is necessary when estimating patient exposure on such systems. This is of particular importance if exposures are to be compared among AEC systems with differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
13
0
Order By: Relevance
“…The phantom consists of an adult male human skeleton embedded in tissue simulating plastic [17,18]. It is designed to simulate an average large (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…The phantom consists of an adult male human skeleton embedded in tissue simulating plastic [17,18]. It is designed to simulate an average large (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…In order to simulate the attenuation of x-rays by a patient in neuro-EIGIs, a custom phantom is used with the test objects to mimic the attenuation of x-rays by a human head. While the ANSI/AAPM head phantom has been recommended for lateral projections [2.5 cm acrylic + 2 mm Al + 10 cm acrylic + 1 mm Al + 2.5 cm of acrylic (Figure 6)] [9] , it has been reported that this phantom is not suitable for measurements involving frontal skull imaging as used in most neuro-EIGI procedures [10] . For this experiment, a head phantom is used that consists of 2.5 cm acrylic + 7 mm Al + 10 cm acrylic + 6 mm Al + 2.5 cm of acrylic and was constructed using NEMA phantom blocks (Figure 7).…”
Section: Methodsmentioning
confidence: 99%
“…The PEP is lightweight and transportable. It is constructed of readily available materials and accurately simulates the standard patient's attenuation properties [13,14].…”
Section: Introductionmentioning
confidence: 99%